PENGARUH QUICK RATIO, DEBT TO EQUITY RATIO, INVENTORY TURNOVER DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011 â€“ 2015 - Sri Ayem; Tri Wahyuni; Suyanto Suyanto (AKUNTANSI DEWANTARA, 2017)
The aim of this study was to examine the effect of QR, DER, IT and NPM simultaneously and partially to profit growth in manufacturing companies that listed in Indonesia Stock Exchange in the period 2011-2015. The population in this study was all manufacturing companies that listed in Indonesia Stock Exchange. The research samples was determined by using purposive sampling technique, with predetermined criteria, so that obtained 13 manufacturing companies that qualify as the samples. The data that used in this study was obtained from secondary source. This study used multiple linear regression method as an analysis technique. The regression test results showed that QR, DER, IT and NPM simultaneously have a significant positive effect on profit growth. Partially, QR IT, DER has no significant positive and NPM has a significant positive effect to profit growth in manufacturing companies that listed in Indonesia Stock Exchange in the period 2011-2015.Â Keywords: Financial Ratio, Quick Ratio, Debt to Equity Ratio, Inventory Turnover, Net Profit Margin and Profit Growth.